PENGARUH KUALITAS PELAYANAN DAN EXPERIENTAL MARKETING TERHADAP LOYALITAS WISATAWAN DI DANAU SIDIONI KECAMATAN RONGGUR NIHUTA KABUPATEN SAMOSIR (STUDI KASUS DANAU SIDIHONI) - Fransiska Tiurma Damanik; Purba, Parlindungan; Saudaranta Tarigan; Togar Sijabat; Yon Sidek Sagala (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2025)
This research was conducted to determine the influence of service quality and experiential marketing on tourist loyalty in Danauu Sidihoni, Ronggur Nihuta District, Samosir Regency, partially and simultaneously. The research method used is a quantitative method. The population in this study were tourists who came to visit Lake Sidihoni, Ronggur Nihuta District, Samosir Regency and the sample for this study was 90 respondents. The results of the research after analysis show that in a partial test the variables of service quality and experiential marketing have a significant or positive influence on tourist loyalty in Lake Sidihoni, Ronggur Nihuta District, Samosir Regency. This is proven that H1 has a calculated t value of 4,651> 1.662 t table and a significance value of 0.000 < 0.05, so H1 is accepted and H0 is rejected. Meanwhile, H2 is proven by the calculated t value of 5,426 > 1.662 t table and a significance value of 0.000 < 0.05, so H2 is accepted and HO is rejected. The results of the research after analysis show that simultaneously the variables of Service Quality and Experiential Marketing are in Danauu Sidihoni, Ronggur Nihuta District, Samosir Regency. This is proven by the calculated f value of 225,285> 3.10 and a significance value of 0.000 < 0.05, then H1, H2 are accepted and H0 is rejected. Variations in the Tourist Loyalty variable are determined by the two independent variables, namely Service Quality and Experiential Marketing, amounting to 83%, while the remaining 17% is influenced by other variables not used in this research.